A Study Of Factors Delivering Competitive Edge In Employee Retention - et. al., Ms Eti Mangal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Employee retention involves time, money and a whole lot of efforts. When an employee leaves an Organization, the process of employee recruitment & retention starts all over again. This revolving door of employee retention is a major cost factor for Organizations all over the world. This study finds the stem which gives a competitive edge in employee retention. Descriptive research method is used. Data collection is done from primary sources, with the help of a questionnaire. Cronbach’s alpha test is used as a pilot test. A total of 200 samples are taken for the analysis. Secondary data is used for literature review. For data analysis, SPSS software is used. Multiple regression linear analysis and frequency analysis is used to test the hypothesis.